User and Gratifications Theory in Knowing Donation Intentions During Live Streaming - Veriansyah, Satria (Journal of Social Science and Business Studies, 2024)
This study investigates the factors that influence viewers' donation intentions to content creators in the context of live streaming in Indonesia by applying the Uses and Gratifications Theory (UGT). This research framework focuses on four independent variables, namely entertainment, escapism, social interaction, and social identity, which influence the dependent variable of donation intention. This quantitative study involved 189 respondents through a purposive sampling technique, with data collected using an online questionnaire and analyzed using regression analysis. The results show that the research model explains 52.7% of the variance in donation intention, with all independent variables contributing statistically significant (p < 0.05). Entertainment is the factor with the largest influence (β=0.829), followed by social interaction (β=0.358), social identity (β=0.178), and escape (β=0.141). These findings emphasize the importance of entertainment value, emotional connection, and community identity in motivating financial support from audiences. This research provides important insights for content creators and digital platforms to increase audience engagement and monetization through content strategy management.